Improved Method for the Determination of Cypermethrin in Sarawak Soils - L.K, Chai; Mohd Tahir, Norhayati; H.C.B, Hansen (Malaysian Journal of Science, 2007)
A gas chromatographic method was developed to determine cypermethrin residues in top and subsoil horizons of three types of Sarawak soils, viz. Semongok (Paleudults), Tarat (Udorthents) and Balai Ringin (Kandiudults) soils. Fourteen different horizons of top and subsoils varying in content of clay (6 - 67 %) and soil organic carbon (0.22 - 2.20 %) were used in the study. Soil samples were spiked with cypermethrin at three concentration levels (0.01, 0.1 and 1 mg/kg) and subsequently extracted for one hour with hexane and acetone at room temperature. This extraction was then followed by liquid-liquid extraction with dichloromethane before determination of cypermethrin by use of GC-ECD. There were no interfering peaks seen in GC chromatograms and therefore no clean-up of the extracts was needed. The recoveries ranged between 80.0 % and 101.2 % with standard deviations ranging between 0.6 % and 9.9 %. It was found that addition of 10 ml water per 10 gram of soil prior to the extraction improved the recovery substantially. The recoveries decreased with soil depth as the clay content increased. The limits of detection were in the range of 1.1 µg/kg to 5.9 µg/kg, which is as good as the similar ECM method used for determination of deltamethrin. In conclusion the method is versatile for rapid determination of cypermethrin in clayey tropical top and subsoils of Sarawak.